Penentuan Kelas Massa Batuan Menggunakan Metode Rock Mass Rating pada Lereng di Kecamatan Walenrang, Kabupaten Luwu, Sulawesi Selatan - Saputra, Apriadi; Zeffitni, Zeffitni; Arum, Deno Ambar; Uno, Djamal Adi Nugroho; Mumin, Risqa Permatasyara (-, 2025)
This study aims to analyze slope stability in Walenrang District, Luwu Regency, South Sulawesi, using the Rock Mass Rating (RMR) method. The research area lies along the Walenrang–Toraja main route, which is composed of volcanic and sedimentary rocks affected by an intensive joint system. Field investigations were conducted using the scanline method to obtain geotechnical parameters such as unconfined compressive strength (UCS), Rock Quality Designation (RQD), discontinuity spacing and condition, and groundwater condition. Based on Schmidt Hammer test results, the rock’s compressive strength was 64 MPa with an RQD value of 97%, indicating excellent rock quality. The weighting of six key parameters produced an RMR value of 69, classifying the rock mass as Class II (good rock). This finding indicates that the slopes at the research location are still in good condition.